New Insights into Chlamydiae Persistence: An Energy Metabolism Strategy?. (April 2013) - Di Pietro, M.; Filardo, S.; De Santis, F.; Sessa, R.
Chlamydiaceae is a family of obligate intracellular bacteria generally considered energy parasites. Several studies have suggested that Chlamydiae are capable of independently producing energy and, more importantly, several genes involved in the energy metabolism are up-regulated during the persistent state. Thus, it has been suggested that chlamydial persistence could be a complex and flexible metabolic strategy designed to favor a lengthy survival in the host cell by evading the immune response. In conclusion, more detailed studies on the shift in the chlamydial energy metabolism, from the active to the persistent form, may be helpful in future to determine whether chlamydial persistence observed in vitro does occur in vivo and whether chronic sequelae of chlamydial diseases may be related to the persistence.